Profile Characteristics of X-ray film used in Radiology Hospital/Health Center/Clinic in Semarang - Ardi Soesilo Wibowo; Johanes Dahjono; Agung Nugroho Setiawan (Poltekkes Kemenkes Semarang, 2014)
The purpose of this study was to determine the characteristics of the X-ray film profile and X-ray films that have the optimal characteristics. This study was conducted on four X-ray films with different brands that are used in 13 radiology department hospital/health center/Clinics in Semarang, called A film, B film, C film and D film. Characteristic curve of each X-ray film was obtained by sensitometry method and measurement results are used to determine the value of basic fog, contrast film (average gradient), latitude and film speed. The results of the study, the characteristics profile of films that have fog basic values lower or equal 0.22 (≤ 0.22) are A, B and D films except C film. Contrast highest to lowest owned B, A, C and D films. Range from the highest to low of film latitude is D film, C film , A film and B film. Speed films produced relatively similar for all X-ray film. Optimum characteristic profile films shown in the B film. The use of X-ray film in a shooting radiograph should pay attention to the type of object being examined to produce optimal quality radiographs and understand each characteristic profile of X-ray films are used.